On Commutativity of Near-Rings with Outer \((σ ,τ)\)-\(n\)-derivations - Leerawat, Utsanee; Aroonruviwat, Pitipong (Communications in Mathematics and Applications, 2021)
In this paper we investigate some appropriate conditions involving outer \((σ ,τ)\)-\(n\)-derivations for a near ring to be a commutative ring.
Keywords: Derivations; Rings; Near-rings; Prime rings; Commutative